INFLUENCE OF STEAM-TO-BIOMASS RATIO ON SYNGAS YIELD AND COMPOSITION IN THE INDUCTION HEATING GASIFICATION OF MUNICIPAL SOLID WASTE - Imron Rosyadi; Yusvardi Yusuf; Sunardi Sunardi; Shofiatul Ula; Dhimas Satria; Elang Daffa Setiadji (Trends in Mechanical Engineering Research, 2026)
This is This study explores the Influence of Steam-to-Biomass Ratio on Syngas Yield and Composition in the Induction Heating Gasification of Municipal Solid Waste (MSW). The aim was to investigate how varying the steam-to-biomass ratio (SBR) affects the yield and composition of syngas during MSW gasification using induction heating. The objectives were twofold: first, to determine the optimal SBR that maximizes hydrogen (H₂) produc-tion in syngas, and second, to analyze the impacts on other syngas compo-nents such as carbon monoxide (CO), carbon dioxide (CO₂), and methane (CH₄). Experimental tests were conducted using an updraft reactor with an induction heating system, maintaining a constant MSW feed rate while ad-justing SBR from 0.56 to 2.09. Gas chromatography was employed to ana-lyze syngas composition, focusing on H₂, CO, CO₂, and CH₄. Key findings indicate that increasing SBR enhances hydrogen production significantly. At an optimal SBR of 2.09, hydrogen content peaked at 36.203%, demonstrat-ing the efficacy of steam in promoting gasification efficiency. Concurrently, CO concentrations decreased with higher SBR values due to intensified wa-ter-gas shift reactions. The study also highlighted challenges related to by-product formation, particularly tar and char residues. Tar production peaked at 9.68 grams under low SBR conditions (0.56), emphasizing the critical role of precise steam control in minimizing tar contamination. Char formation averaged 4 grams across SBR variations, influenced by biomass characteris-tics and reactor cleanliness. These findings contribute to advancing sustaina-ble waste-to-energy practices by optimizing gasification parameters tailored to local MSW compositions. Future research should focus on refining gasifi-cation technologies and conducting comprehensive techno-economic as-sessments to evaluate scalability and cost-effectiveness in diverse environ-mental settings.